Pengembangan Bahan Ajar Interaktif Materi Kehidupan Masyarakat Pada Masa Pra Aksara Di Indonesia - Azman, Muhammad Khairul; Wedi, Agus; Husna, Arafah (JKTP: Jurnal Kajian Teknologi Pendidikan, 2022)
The purpose of this development is to make interactive teaching materials products of public life materials during pre-literacy in Indonesia that are suitable for use in learning for social science subjects in junior high school class VII. This interactive teaching material can be used as a complementary supplement in the learning process so that it can increase students' motivation and interest in learning. This product can be used independently or in groups. Interactive teaching materials are packaged with a powerpoint show display, using personal computers (PCs), laptops and the like. The detailed content of the material and the interface design are designed with a user friendly system so that it is easy for users to understand and use. This development procedure uses the model of Lee & Owens, 2004. Responses from media experts and material experts to this interactive teaching material get a positive response. The trial of the use of interactive teaching materials was carried out on grade VII junior high school students. Overall, interactive teaching materials on people's life during pre-literacy in Indonesia are suitable for use in learning.Abstrak Tujuan dari pengembangan ini yakni membuat produk bahan ajar interaktif materi kehidupan masyarakat pada masa pra aksara di indonesia yang layak digunakan pada pembelajaran untuk mata pelajaran ilmu pengetahuan sosial SMP kelas VII. Bahan ajar interaktif ini bisa digunakan sebagai suplemen pelengkap didalam proses pembelajaran sehingga bisa menambah motivasi dan minat belajar anak didik. Produk ini dapat digunakan secara mandiri maupun kelompok. Bahan ajar interaktif dikemas dengan tampilan powerpoint show, pemanfaatannya menggunakan personal computer (pc), laptop dan sejenisnya. Rincian konten materi dan desain interfacenya dirancang dengan sistem user friendly agar mudah dimengerti dan dipakai oleh penggunanya. Prosedur pengembangan ini menggunakan model Lee & Owens, 2004. Tanggapan dari ahli media dan ahli materi terhadap bahan ajar interaktif ini mendapatkan respon positif. Uji coba pemanfaatan bahan ajar interaktif dilakukan kepada siswa SMP kelas VII. Secara keseluruhan bahan ajar interaktif materi kehidupan masyarakat pada masa pra aksara di indonesia layak digunakan dalam pembelajaran.